1990
DOI: 10.1016/s0022-5347(17)39608-8
|View full text |Cite
|
Sign up to set email alerts
|

Progression and Survival after Renal-Conserving Surgery for Renal Cell Carcinoma: Experience in 104 Patients and Extended Followup

Abstract: Of 104 patients who underwent a conservative operation for renal cell carcinoma 42 underwent partial nephrectomy, 60 underwent enucleation and 2 underwent a combination of these procedures. A total of 14 patients required an extracorporeal operation with autotransplantation. Forty patients had bilateral renal cell carcinoma (20 were synchronous and 20 were asynchronous) and 39 had either a solitary kidney or a poorly functioning contralateral renal unit. An operation was performed in the presence of a normal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
0
13

Year Published

1992
1992
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(119 citation statements)
references
References 30 publications
5
97
0
13
Order By: Relevance
“…The rates of local recurrence for smaller tumors after partial nephrectomy are 1.4% to 2% versus 10% for larger tumors. [81][82][83] The panel recommends yearly chest imaging (chest radiograph or CT) for 3 years, then as clinically indicated thereafter, and recommends imaging of the pelvis, CT or MRI of the head and spine, or bone scan performed as clinically indicated.…”
Section: Follow-up After Nephrectomy For Stages I-iiimentioning
confidence: 99%
“…The rates of local recurrence for smaller tumors after partial nephrectomy are 1.4% to 2% versus 10% for larger tumors. [81][82][83] The panel recommends yearly chest imaging (chest radiograph or CT) for 3 years, then as clinically indicated thereafter, and recommends imaging of the pelvis, CT or MRI of the head and spine, or bone scan performed as clinically indicated.…”
Section: Follow-up After Nephrectomy For Stages I-iiimentioning
confidence: 99%
“…But only a few studies in the 1980s and early 1990s reported on the use of this technique for treating small RCC tumors, and they showed similar 5-yr survival rates to those of partial nephrectomy [16][17][18][19]. Recently, other retrospective analyses confirmed that TE can be safely used for treating pT1a-pT1b RCC tumors, and it is not associated with any greater risk of local recurrence than is partial nephrectomy [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of renal cell carcinoma has greatly improved owing to advances in imaging modalities and surgical techniques (4,5), with the present reference-standard technique for treatment of renal tumors being radical nephrectomy. However, small localized renal tumors have also been successfully treated with partial nephrectomy (6)(7)(8)(9)(10)(11)(12). A minimally invasive treatment capable of causing the selective destruction of large tumors while preserving kidney function might have a positive effect on the outcomes of quality of life and dialysis-free survival.…”
mentioning
confidence: 99%